-2*[3-(6)^2 :(-9)]-2*[5-(-7)]=?
Răspunsuri la întrebare
Răspuns de
2
-2[3-(6)²:(-9)]-2[5-(-7)]=
-2[3-36:(-9)]-2(12)=
-2(3+4)-24=
-2(7)-24=-14-24=-38
succes
-2[3-36:(-9)]-2(12)=
-2(3+4)-24=
-2(7)-24=-14-24=-38
succes
Răspuns de
4
=-2•[3+36:(-9)]-2•[5-(-7)]
=-2•(3-4)-2•2•12
=-2•(-1)-24
=+2-24
=-22
Sper ca nu am gresit!Spor la scris!
=-2•(3-4)-2•2•12
=-2•(-1)-24
=+2-24
=-22
Sper ca nu am gresit!Spor la scris!
Alte întrebări interesante
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă